Organizational Culture as Equilibrium? Rules Versus Principles in Building Relational Contracts - Robert S. Gibbons; Manuel Grieder; Holger Herz; Christian Zehnder (Center for Economic Studies and ifo Institute (CESifo), 2019)
Effective organizations are able not only to coordinate their members on efficient strategies but also to adapt members' strategies to unforeseen change in an efficient manner. We explore whether part of organizational culture - namely, relational contracts that facilitate both coordi-nation and adaptation - enable organizations to achieve these ends. In a novel experiment, we explore how parties establish such relational contracts, whether they achieve efficient coopera-tion, and how they adapt to exogenous shocks. Specifically, we test the hypothesis that basing a relational contract on general principles rather than specific rules is more successful in achieving efficient adaptation. In our Baseline condition, we observe that pairs who articulate general principles achieve significantly higher performance than those who rely on specific rules. The mechanism underlying this correlation is that pairs with principle-based agreements are more likely to expect their pair to take actions that are consistent with what their relational contract prescribes. To investigate whether there is a causal link between principle-based agreements and performance, we implement a “Nudge” intervention to foster principle-based relational con-tracts. The Nudge succeeds in motivating more pairs to formulate principles and in making pairs significantly more likely to select efficient initial choices. However, the intervention fails to increase performance in the long run. Our results suggest that principle-based relational con-tracts may improve organizational performance, but our results also illustrate the difficulty of building such an organizational culture, which is consistent with the idea that high-performing relational contracts constitute a competitive advantage only if they are difficult to imitate.
Keywords: D02; D23; L14; 330; organization economics; adaptation; relational contracts